Ribozymes and RNA catalysis - Lilley, David M. J.; Eckstein, Fritz (RSC Publishing, 2008)
The discovery that RNA could act as a macromolecular catalyst in the cell, signified a paradigm shift in molecular biology. Ribozymes and RNA Catalysis takes the reader through the origins of catalysis in RNA and necessarily includes significant discussion of structure and folding. The main focus of the book concerns chemical mechanism with extensive comment on how, despite the importance of RNA catalysis in the cell, its origins are still poorly understood and often controversial. The reader is given an outline of the important role of RNA catalysis in many aspects of cell function, including RNA processing and translation. There has been a significant coming together in the field of RNA in recent years and this book offers a compelling review of the whole field to date. Written by leading experts in their field, who in turn review the structural and mechanistic data for all known ribozymes this book is well suited for undergraduates, postgraduates and researchers in catalytic chemistry as well as those in related fields who require a unique overview of the subject.